Synergy Between Spiritual Education and Quality Management in the Modern Era - Hartinah; Putra, Fikri Hakim; Maharani, Nur Fitriani; Bodori, Susanti (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
Education in the modern era faces challenges from rapid technological advancement and globalization. The primary focus is often directed toward developing practical skills and critical thinking abilities, while spiritual and moral values tend to be overlooked. This research aims to integrate spiritual education into quality management to produce academically excellent individuals with strong moral integrity. This study explores the role of spiritual education in shaping individual character and morals and analyzes its impact on the overall quality of education. The method used in this research is a literature review, where the researcher collects and analyzes various literature sources, including books, articles, and relevant academic journals. The results indicate that spiritual education is crucial in helping students understand their identity, achieve inner peace, and enhance their mental and emotional well-being. Spiritual education in quality management has proven to create a positive work culture, strengthen collaboration, and reduce conflicts within the educational environment. This research also finds that individuals with a deep spiritual understanding are better prepared to face life challenges and can make wise decisions. In conclusion, integrating spiritual education and quality management is essential for shaping a generation characterized by integrity, resilience in the face of change, and the ability to contribute to creating a just and prosperous society.